2014
DOI: 10.1007/s11010-013-1957-3
|View full text |Cite
|
Sign up to set email alerts
|

miR-143 suppresses osteogenic differentiation by targeting Osterix

Abstract: Osterix (Osx) is an essential transcription factor for osteoblast differentiation and bone formation. However, the knowledge of the regulation of Osx expression is poor. MicroRNAs (miRNAs), a class of small non-coding RNAs, play critical roles in numerous biological processes, including the proliferation, differentiation, and survival of cells and organisms. Herein, we aimed to explore the effect of miR-143 on Osx expression and osteogenic differentiation. miR-143, which was suppressor of the osteogenic differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 21 publications
1
50
1
Order By: Relevance
“…Li et al reported that miR-143 suppressed osteogenic differentiation by targeting Osx in osteoblastic MC3T3-E1 cells [84]. MiR-143-mimic transfection upregulated Osx , alkaline phosphatase (ALP) and osteocalcin levels, whereas miR-143 inhibitor reduced their expression.…”
Section: The Role Of Mirnas In Osteoblastsmentioning
confidence: 99%
“…Li et al reported that miR-143 suppressed osteogenic differentiation by targeting Osx in osteoblastic MC3T3-E1 cells [84]. MiR-143-mimic transfection upregulated Osx , alkaline phosphatase (ALP) and osteocalcin levels, whereas miR-143 inhibitor reduced their expression.…”
Section: The Role Of Mirnas In Osteoblastsmentioning
confidence: 99%
“…It was recently revealed that miRNAs have been involved in mediating the osteogenic differentiation of osteoblasts and mesenchymal stem cells (MSCs). MiR-143 and miR-145 were decreased in osteogenic differentiation, and their overexpression suppressed osteogenic differentiation by targeting Osterix and Sp7 transcription factor 7 (Sp7) in vitro, respectively [12,13]. MiR-155 is induced by Interferon-β and inhibits osteoclast differentiation by targeting suppressor of cytokine signaling 1 (Socs1) and microphthalmia-associated transcription factor (Mitf), two essential regulators of osteoclastogenesis [14].…”
Section: Introductionmentioning
confidence: 99%
“…However, a relationship has not been confirmed beyond the finding of reduced Osx mRNA [99]. In contrast, miR-143 [100,101], miR-145 [100], miR-214 [102] and miR-637 [103] suppress osteogenic differentiation by directly targeting Osx. Due to the ability of miR-322 to directly target Tob2 , which normally helps to degrade Osx, Osx mRNA is stabilized, allowing osteoblast differentiation to occur [104].…”
Section: Micrornas Associated With the Mesenchymal State And Mesenchymentioning
confidence: 99%